Development of a Novel Positron Emission Tomography (PET) Radiotracer Targeting Bromodomain and Extra-Terminal Domain (BET) Family Proteins - Bai, Ping; Lan, Yu; Wang, Hao; Chen, Zude; Fiedler, Stephanie; Striar, Robin; Lu, Xiaoxia; Wang, Changning (Frontiers in Molecular Biosciences, 2020)
Bromodomain and extra-terminal domain (BET) family proteins have become a research focus because of their close relationship with various diseases. With a suitable imaging probe, the non-invasive imaging technique, positron emission tomography (PET), provides a powerful tool to visualize and quantify the BET family proteins that accelerating the investigation of this domain. Herein, we describe the development of a promising PET probe, [11C]1, specifically targeting BET family proteins based on the potent BET inhibitor CF53. [11C]1 was successfully radio-synthesized with good yield and high purity after the optimization of radio-labeling conditions. The in vivo bio-activities evaluation of [11C]1 was performed through the PET imaging in rodents. The results demonstrated that [11C]1 has favorable uptake in peripheral organs and moderate uptake in the brain. Further blocking studies indicated the high binding specificity and selectivity for BET proteins of this probe. Our findings suggest that [11C]1 is a promising BET PET probe for BET proteins as well as epigenetic imaging.